Trends and variation in the incidence of hip fracture in England before, during, and after the COVID-19 pandemic (2014–2024): a population-based observational studyResearch in context - James Webster; Emre Oguzman; Eva J.A. Morris; Sasha Shepperd; Xavier L. Griffin; Antony Johansen; Raphael Goldacre (The Lancet Regional Health. Europe)
Summary: Background: Hip fractures are a common serious injury in older adults. The COVID-19 pandemic had a substantial impact on hip fracture prevention services, but contemporary data on incidence are scarce. We investigated recent trends and variation in the incidence of hip fracture in England. Methods: A population-based study was conducted of hip fracture hospital presentations in adults aged ≥50 years using English national secondary care data (January 2014–October 2024). Trends in incidence were compared across pre-pandemic (January 2014–February 2020), pandemic (March-2020–July-2021), and post-pandemic periods (August 2021–October 2024). Variation by age, sex, and area-level deprivation were explored. Findings: From 2014 to 2024, there were 704,762 hip fractures in 669,101 patients. Age-standardised incidence rates steadily declined from 2014 to 2019 from a mean monthly rate of 28.0–26.4 per 100,000 population. Incidence rates were below expected levels during the pandemic (IRR 0.96, 95% CI 0.94–0.97) but above expected levels in the post-pandemic period (IRR 1.03, 95% CI 1.01–1.04), resulting in 5595 more hip fractures than expected from August 2021 to October 2024. Hip fractures were more common in women, but temporal trends were consistent by sex. Incidence rates were higher in the most compared with the least deprived quintile; these inequalities remained largely unchanged by 2024 (IRR, 95% CI 1.67 [1.45–1.93] in men; 1.30 [1.19–1.42] in women). Interpretation: This study highlights an excess of hip fracture presentations to hospital since the COVID-19 pandemic, and continued disparities in incidence by deprivation, despite an overall decreasing long-term trend. More equitable prevention strategies are needed, such as through more widespread screening for fracture risk and better coverage of fracture liaison services. Funding: Authors are supported by the NIHR Oxford BRC.